Decisions Not to Report Sexual Assault: A Comparative Study among Women Living in Japan Who Are Japanese, Korean, Chinese, and English-Speaking - Dussich, John P. (International journal of offender therapy and comparative criminology, 2001)
A nationwide survey was conducted comparing Japanese, Chinese, Korean, and English-speaking women in Japan. Variables focused on demographics, attitudes, social conditions, and culture. Japanese women had a different pattern of behavior from the other three groups. The greatest differences were between Japanese and English-speaking. The main reasons given for not reporting were the following: victim did not take the event seriously, victim thought she was too young, victim thought reporting would cause trouble, victim expected rude police, victim expected embarrassment, victim expected police to violate her confidentiality, victim expected offender's revenge, and victim expected that the offender/acquaintance would get into trouble. These data suggest a much larger dark figure of sexual assault than is reported, especially among those who are not Japanese and those whose offenders were known. Police statistics do not accurately reflect the number of women sexually assaulted, nor is there any systematic information collected explaining their reporting behavior